Effect of punching on physical and mechanical properties of leathers: Focus on car seat covers. (December 2019) - Roh, Eui Kyung
As a lot of time is spent in the car, the comfort of not only the car seat but also the car seat cover itself has become of increasing importance. With increasing use of ventilated seats, the control of the physical and mechanical properties of leather in response to punching has become of prime importance in the design of car seats. This study evaluated the changes in the physical and mechanical properties of leather due to punching and proposes optimum punching intervals for car seats. Sixteen types of leather, punched at three spatial intervals (2, 3, and 5 mm), were evaluated in terms of their apparent density, softness, coefficient of friction, warm-cool feeling, and mechanical properties. Leather punching affected its physical and mechanical properties. However, there were differences in punching intervals that significantly affected each property, including the mechanical properties. Depending on the performance required when developing a product, a suitable punching interval must be selected. Therefore, punching at 5 mm intervals is preferred for obtaining physical and mechanical properties similar to those of untreated leathers, and punching at 3 mm intervals is recommended for achieving more softness. On the contrary, punching at 2 mm intervals increases air permeability but decreases dimensional stability.